Statistical Wind Energy Analysis and Wind Persistence Assessment for Cordoba And Sucre Departments' Weather Stations in The Caribbean Region of Colombia (2020)
A statistical analysis is carried out on the behavior of wind speed at meteorological stations located in the Caribbean Region of Colombia, in order to establish and identify the potential available in wind energy to be used as a renewable energy source, this by through the use of rigorous periodic studies, carried out by the Colombian Institute of Environment, Meteorology and Hydrology (IDEAM), to have efficient energy management and encourage the start-up of wind farms, which satisfy the energy demand necessary for the supply of Vulnerable Populations in the Colombian nation, therefore, the meteorological stations and their location are described, a wind analysis is made at different heights and roughness of the study terrain, and wind persistence studies are carried out using the autocorrelation function (ACF), behavioral analyzes are made Hourly and annual wind rate, for the meteorological stations described, in addition, graphs of the wind direction or wind roses are presented, with greater stability in the annual periods. From which an analysis could be established that allows the use of wind energy potential to be viewed by adequately reaching the behavior of the wind for meteorological stations in the departments of Córdoba and Sucre located in the Caribbean Region. The department of Córdoba presents, according to its meteorological stations, an average wind speed value ranging from 1.3 m/s to 1.4 m/s, while in the department of Sucre, values of average wind speed of 0.85 m/s to 1.7 m/s.